Changes of uterocervical angle and cervical length in early and mid-pregnancy and their value in predicting spontaneous preterm birth - Zhang, Miaomiao; Li, Shuilan; Tian, Chao; Li, Min; Zhang, Baofang; Yu, Hongkui (Frontiers in Physiology, 2024)
We believe that our study is a significant contribution because we identified the combination of uterocervical angle (UCA) and cervical length (CL) has a better ability to predict preterm birth than cervical length or uterocervical angle alone. A more obtuse uterocervical angle or a shorter cervical length is associated with an earlier spontaneous preterm birth. The uterocervical angle increases from early to mid-pregnancy, while the cervical length decreases from early to mid-pregnancy. Further, we believe that this paper will be of interest to the readership of your journal because it matches your researches topics about aging in female infertility and pathologic pregnancy.